Factors Affecting Cryopreservation of Domestic Cat (Felis catus) Epididymal Spermatozoa - Natalia Gañán; Ana Sanchez-Rodriguez; Eduardo R. S. Roldan (Animals)
Sperm cryopreservation is a powerful tool for the conservation of endangered species, but its application requires adapting protocols to particular species, due to differences in sperm structure, function, and cryosensitivity. Research on the biology of endangered felids primarily relies on the domestic cat as an experimental model. Semen from live animals can be collected using several methods. However, in animals that die due to roadkill or in the field, spermatozoa must be retrieved from the epididymis. Differences may exist in the cryosensitivity of epididymal and ejaculated sperm due to the influence of secretions from accessory genital glands. We analyzed the effects of several factors on the motility and acrosomal integrity of cryopreserved cat epididymal spermatozoa, including cooling rate, storage system, time and temperature of straw loading, and the freezing method in nitrogen vapors. There were no significant differences in motility or acrosomal integrity at thawing between fast (−0.5 °C/min) or slow (−0.125 °C/min) cooling rates or between loading straws at room temperature versus 5 °C. Post-thaw motility was significantly higher when using straws compared to pellets and when freezing in nitrogen vapors at two levels rather than at a single level. Additionally, interactions between the loading temperature of straws and both motility and acrosomal integrity were not significant. These results are important for standardizing protocols to cryopreserve feline epididymal sperm, facilitating the rescue of genetic material from endangered species in the field.